2015
DOI: 10.1007/s00198-015-3162-6
|View full text |Cite
|
Sign up to set email alerts
|

A survey of outcomes and management of patients post fragility fractures in China

Abstract: The osteoporotic hip and vertebral fractures caused excess mortality rates in this population of Mainland China. The current diagnosis and medical treatment following the fragility fractures is still insufficient in Mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 36 publications
0
42
0
1
Order By: Relevance
“…Seven studies were retrospective in design [12, 2328], identifying hip fracture patients from hospital, health care or medical claims databases; the remainder were prospective (i.e. participants were identified on admission or discharge from hospital).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies were retrospective in design [12, 2328], identifying hip fracture patients from hospital, health care or medical claims databases; the remainder were prospective (i.e. participants were identified on admission or discharge from hospital).…”
Section: Resultsmentioning
confidence: 99%
“…One study was a cohort of patients with trochanteric fractures treated by Ender nailing; this study was included as it reported on change in self-care outcomes, for which few studies were identified [29]. The majority of studies included patients aged 60 or 65 years and over, although nine studies included patients aged 50 years or over [12, 18, 24, 25, 3036]. Eight studies specifically enrolled patients with hip fracture as a result of low-impact trauma or falls [12, 23, 27, 33, 3639]; one included patients with fractures obtained from low to moderate energy trauma [30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations